TOXIC POSITIVITY: THE DYNAMICS OF INTERPERSONAL COMMUNICATION ON MEDIA X IN THE ERA OF CANCEL CULTURE - Harahap, Muhammad Rizkie Habibie; Yusniah, Yusniah (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to examine the dynamics of interpersonal communication on the Media X platform within the context of the phenomena of toxic positivity and cancel culture. These two phenomena represent a paradox of digital culture: on one hand, there is an incessant push for maintaining positivity, often dismissing the validity of negative emotions; on the other hand, there is the rise of collective cancellation practices that can create intense social pressure. This research employs a qualitative approach using a netnographic strategy, supported by content analysis of user-generated posts and interactions. Data were collected through digital observation, documentation of online conversations, and the use of Brand24 as a social media analytics tool. The findings reveal that toxic positivity is frequently normalised through phrases such as